Dystonia as a prominent presenting feature in developmental and epileptic encephalopathies: A case series. (September 2021) - Dzinovic, Ivana; Škorvánek, Matej; Necpál, Ján; Boesch, Sylvia; Švantnerová, Jana; Wagner, Matias; Havránková, Petra; Pavelekova, Petra; Haň, Vladimír; Janzarik, Wibke G.; Berweck, Steffen; Diebold, Isabel; et al.
Abstract: Introduction: Although there has been increasing recognition of the occurrence of non-epileptic involuntary movements in developmental and epileptic encephalopathies (DEEs), the spectrum of dystonic presentations associated with these conditions remains poorly described. We sought to expand the catalogue of dystonia-predominant phenotypes in monogenic DEEs, building on the recently introduced concept of an epilepsy-movement disorder spectrum. Methods: Cases were identified from a whole-exome-sequenced cohort of 45 pediatric index patients with complex dystonia (67% sequenced as parent-child trios). Review of molecular findings in DEE-associated genes was performed. For five individuals with identified DEE-causing variants, detailed information about presenting phenotypic features and the natural history of disease was obtained. Results: De-novo pathogenic and likely pathogenic missense variants in GABRA1, GABBR2, GNAO1, and FOXG1 gave rise to infantile-onset persistent and paroxysmal dystonic manifestations, beginning in the limb or truncal musculature and progressing gradually to a generalized state. Coexisting, less prominent movement-disorder symptoms were observed and included myoclonic, ballistic, and stereotypic abnormal movements as well as choreoathetosis. Dystonia dominated over epileptic neurodevelopmental comorbidities in all four subjects and represented the primary indication for molecular genetic analysis. We also report the unusual case of an adult female patient with dystonia, tremor, and mild learning disability who was found to harbor a pathogenic frameshift variant in MECP2 . Conclusions: Dystonia can be a leading clinical manifestation in different DEEs. A monogenic basis of disease should be considered on the association of dystonia and developmental delay-epilepsy presentations, justifying a molecular screening for variants in DEE-associated genes. Highlights: Epilepsy and non-epileptic abnormal movements can co-exist. Five of 45 pediatric dystonia patients had variants in developmental and epileptic encephalopathy-related genes. Mutant cases had complex dystonia but only minimal epileptic comorbidity. Epilepsy and dystonia can form a phenotypical continuum within the category of neurodevelopmental disorders. Epilepsy-related genes should be considered in genetic screening panels for dystonia.